Report on the “Big Data Training School for Life Sciences”, 18-22 September 2017, Uppsala, Sweden - Pfeil, Juliane; Schulze, Sabrina Kathrin; Zdravevski, Eftim; Hoang, Yen (My University, 2017)
In September 2017 a "Big Data Training School for Life Sciences" took place in Uppsala, Sweden, jointly organised by EMBnet and the COST Action CHARME (Harmonising standardisation strategies to increase efficiency and competitiveness of European life-science research - CA15100). The week programme was divided into handson sessions and lectures. In both cases, insights into dealing with big amounts of data were given. This paper describes our personal experience as students’ by providing also some suggestions that we hope can help the organisers as well as other trainers to further increase the efficiency of such intensive courses for students with diverse backgrounds.